Sex Differences in Human Immunodeficiency Virus Persistence and Reservoir Size During Aging. (6th October 2021) - Gianella, Sara; Rawlings, Stephen A; Dobrowolski, Curtis; Nakazawa, Masato; Chaillon, Antoine; Strain, Matthew; Layman, Laura; Caballero, Gemma; Scully, Eileen; Scott, Brianna; Pacis, Caitleen; Weber, Kathleen M; et al.
Abstract: Background: Sex differences in human immunodeficiency virus (HIV) reservoir dynamics remain underexplored. Methods: Longitudinal samples from virally suppressed midlife women (n = 59, median age 45 years) and age-matched men (n = 31) were analyzed retrospectively. At each time point, we measured sex hormones (by means of enzyme-linked immunosorbent assay) and cellular HIV DNA and RNA (by means of digital droplet polymerase chain reaction). Number of inducible HIV RNA + cells, which provides an upper estimate of the replication-competent reservoir, was quantified longitudinally in a different subset of 14 women, across well-defined reproductive stages. Mixed-effects models included normalized reservoir outcomes and sex, time since antiretroviral therapy (ART) initiation, and the sex-by-time interaction as predictors. Results: At ART initiation, women and men had median (interquartile range [IQR]) CD4 + T-cell counts of 204/μL (83–306/μL) versus 238/μL (120–284/μL), respectively; median ages of 45 (42–48) versus 47 (43–51) years; and median follow-up times of 79.2/μL (60.5–121.1/μL) versus 66.2/μL (43.2–80.6/μL) months. We observed a significant decline of total HIV DNA over time in both men and women ( P < .01). However, the rates of change differed significantly between the sexes ( P < .01), with women having a significantly slower rate of decline than men, more pronounced with age. By contrast, the levels of inducible HIV RNA increased incrementally over time in women during reproductive aging ( P < .01). Conclusions: In contrast to men, in whom the HIV reservoir steadily declines with aging, the HIV reservoir in women is more dynamic. Total HIV DNA (including intact and defective genomes) declines more slowly in women than in men, while the inducible HIV RNA + reservoir, which is highly enriched in replication-competent virus, increases in women after menopause.